2008
DOI: 10.1186/1742-4690-5-60
|View full text |Cite
|
Sign up to set email alerts
|

Viral complementation allows HIV-1 replication without integration

Abstract: Background: The integration of HIV-1 DNA into cellular chromatin is required for high levels of viral gene expression and for the production of new virions. However, the majority of HIV-1 DNA remains unintegrated and is generally considered a replicative dead-end. A limited amount of early gene expression from unintegrated DNA has been reported, but viral replication does not proceed further in cells which contain only unintegrated DNA. Multiple infection of cells is common, and cells that are productively inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
162
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(172 citation statements)
references
References 92 publications
(146 reference statements)
10
162
0
Order By: Relevance
“…Aware of the fact that significant numbers of HIV-1-infected cells contain more than one viral genome (35), we demonstrate a viable crosstalk between integrated and episomal HIV-1 forms, which, similar to an earlier report, allowed recombination between integrase-deficient and wild-type viral genomes (7). Overall, this study demonstrates that chromatinized episomal HIV-1 genomes are subject to epigenetic silencing, which can be alleviated by HDACi, including SCFAs generated by the normal bacterial flora of the gut and thus, strongly indicates that episomal HIV-1 forms and SCFAs could play an important role in the early phases of HIV-1 infection, especially when the initial viral load is low.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Aware of the fact that significant numbers of HIV-1-infected cells contain more than one viral genome (35), we demonstrate a viable crosstalk between integrated and episomal HIV-1 forms, which, similar to an earlier report, allowed recombination between integrase-deficient and wild-type viral genomes (7). Overall, this study demonstrates that chromatinized episomal HIV-1 genomes are subject to epigenetic silencing, which can be alleviated by HDACi, including SCFAs generated by the normal bacterial flora of the gut and thus, strongly indicates that episomal HIV-1 forms and SCFAs could play an important role in the early phases of HIV-1 infection, especially when the initial viral load is low.…”
Section: Discussionsupporting
confidence: 56%
“…These findings suggest that gene expression from nonintegrating HIV-1 forms can potentially affect the life cycle and pathogenesis of HIV-1. This notion was corroborated by a recent report showing the ability of integrated HIV-1 provirus to support packaging of episomally transcribed viral genomes into infectious particles (7).…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Expression of the early HIV-1 tat, rev and nef genes after infection with integration-deficient HIV-1 has been detected repeatedly, but expression levels seem to be too low to promote lategene expression and production of infectious particles (reviewed by Wu, 2004). More recently, however, it has been demonstrated that integration-deficient mutants can be rescued by co-infection with wild-type HIV-1 (Gelderblom et al, 2008). Co-infection with wild-type virus led to late-gene expression from the unintegrated HIV-1 mutant DNA and even transfer of genomic RNA of the IN-deficient mutant into target cells at an unexpectedly high frequency.…”
Section: Potential Benefits Of Rev-mediated Inhibition Of Integrationmentioning
confidence: 99%
“…However, in these experiments, replication of the second virus has not been analysed. If the only effect of Rev during the early phase of the replication cycle is to block integration to prevent genotoxicity, then the data of Gelderblom et al (2008) would actually indicate that the second virus can replicate without integration and therefore contribute to the development of sequence diversity.…”
Section: Potential Benefits Of Rev-mediated Inhibition Of Integrationmentioning
confidence: 99%